Subjective age and performance based decisions: mediating effects of rater goals - Huebner, Lena-Alyeska, author; Cleveland, Jeanette N., advisor; Fisher, Gwenith G., committee member; Shore, Lynn M., committee member; Dik, Bryan J., committee member (Colorado State University. Libraries, 2017)
The present study examined whether subjective age of the rater was associated with an occupational future time perspective (OFTP) and goal orientation, and whether variations in OFTP and goal orientation predicted performance-based recommendations for older employees. Life-span theories, such as Selection, Optimization and Compensation Theory and the Socioemotional Selectivity Theory, suggest that as we age our goals shift from a future focus to a maintenance focus. However, this future versus maintenance orientation may be associated with one's subjective age. That is, individuals who perceived themselves as subjectively younger may have greater future orientation (and lower maintenance orientation) than individuals with subjectively older ages. Using a performance appraisal context, this study investigated whether this re-orientation of goals leads to differing ratings for older employees. A sample of 305 participants provided performance-based recommendations regarding promotions, developmental training, flextime, and regular performance appraisals for vignettes of older employees. Results showed that subjective age was not a significant predictor of performance recommendations although was correlated with both occupational future time perspective and rating goals. Further the relationship between OFTP and performance recommendations was mediated by rating goals. Although subjective age may be a useful alternative age measure, rater OFTP may be more meaningful in understanding variations in ratings of older employees.